Announcement of the broadcast program of the French POW camp Bizerte in Tunisia. . From 'Kriegsgefangenenlager Bizerte Collection'
Announcement of the broadcast program of the French POW camp Bizerte in Tunisia. From 'Kriegsgefangenenlager Bizerte Collection'.